A micro-crosslinking agent and a preparation method thereof, a battery separator and a preparation method thereof
Patent Information
- Application Number
- CN202610888583.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-18
- Publication Date
- 2026-10-16
AI Technical Summary
该方案在共聚过程中存在有端基羧酸结构,电解液为碳酸酯,其在电池中会发生酯交换反应,使得电解液分解产生二氧化碳、一氧化碳等,造成电池鼓包
[0038] This invention provides a solution for enhancing the interfacial wettability of ultra-high molecular weight polyethylene by initiating graft copolymerization with a peroxide initiator to form a lithium battery separator with good wettability.
Smart Images

Figure CN122916845A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to micro-crosslinking synthesis technology, and more specifically, to a multipolar functional group micro-crosslinking agent and an ultra-high molecular weight polyethylene separator. Background Technology
[0002] Ultra-high molecular weight polyethylene (UHMWPE) is a high-end polyolefin material with a unique linear long-chain structure, relatively few branches, and a relative molecular weight typically exceeding 1 million. It possesses excellent wear resistance, high impact strength, resistance to environmental stress cracking, and a low coefficient of friction. Due to these superior properties, UHMWPE materials have been applied in fields such as biomaterials, medicine, and mining.
[0003] In recent years, with the country's vigorous promotion of the development of the new energy field, the development of ultra-high molecular weight polyethylene (UHMWPE) materials has entered a faster track, shifting from general-purpose conventional materials to refined and specialized materials. Especially in the field of lithium-ion battery separators, UHMWPE is mainly used as the base film in wet-process lithium-ion battery separators, with 80% of UHMWPE production capacity used for lithium-ion battery separator production. Meanwhile, it is also widely used in bulletproof vests and high-performance ropes.
[0004] In lithium-ion batteries, the separator is mainly used to separate the positive and negative electrodes. Its pore size, thickness, and other parameters directly affect the battery's capacity, lifespan, and safety. Ultra-high molecular weight polyethylene (UHMWPE) possesses excellent mechanical properties and corrosion resistance, with a melting point typically above 130°C. It also has numerous microscopic polymer chain entanglements. Under high temperatures, UHMWPE melts but does not collapse, exhibiting a gel-like state. This effectively reduces the risk of short circuits caused by sudden temperature increases during battery use.
[0005] While ultra-high molecular weight polyethylene (UHMWPE) possesses the aforementioned advantages, it also exhibits significant drawbacks. UHMWPE is a long-branched polymer formed by the polymerization of ethylene under catalytic conditions. Its low molecular polarity results in poor solvent wettability in lithium batteries. To improve the wettability of UHMWPE to the electrolyte, various modifications have been made, with the core objective being to increase the polarity of the battery separator surface, thereby enabling electrolyte wettability.
[0006] Patent CN120795242A mentions modifying UHMWPE by extruding it with acrylic acid, epoxidized soybean oil, and glycidyl methacrylate. The modified powder exhibits a significantly improved melt index and a reduced contact angle to 80-85°. However, this method involves end-group carboxylic acid structures during copolymerization. Since the electrolyte is a carbonate, it undergoes transesterification in the battery, causing the electrolyte to decompose and produce carbon dioxide and carbon monoxide, leading to battery bulging.
[0007] Patent CN118374972A mentions using tannic acid to modify ultra-high molecular weight polyethylene. It utilizes tannic acid to initiate polymerization on the fiber with an initiator, forming a coating in a short time and improving the interfacial adhesion performance of the product. However, in this solution, tannic acid is difficult to react with the main structure, and it may migrate and fall off during use, eventually entering the battery and affecting battery safety. Summary of the Invention
[0008] This invention provides a micro-crosslinking agent and its preparation method, as well as a battery separator and its preparation method. To improve the wettability of the ultra-high molecular weight polyethylene (UHMWPE) lithium battery separator to the electrolyte, non-polar graft groups are introduced onto the UHMWPE to improve the compatibility of the carbonate with the graft groups. The grafted segments are still mainly carbon-carbon bonds and will not affect the main chain. This invention chooses a chemical crosslinking method, while improving the functional group structure, avoiding possible transesterification reactions inside the battery, and simultaneously improving the wettability of the carbonate to the separator.
[0009] To achieve the above objectives, the technical solution of the present invention is as follows:
[0010] A micro-crosslinking agent, as shown in Formula I,
[0011] I
[0012] Among them, R 1 R 2 The functional groups are independent of each other and are saturated hydrocarbon functional groups with C6 or less, preferably methyl, ethyl, or propyl.
[0013] As a preferred embodiment, the microcrosslinking agent is used to prepare chemically modified graft copolymers.
[0014] Furthermore, as a preferred embodiment, the microcrosslinking agent is used as a grafting compound for ultra-high molecular weight polyethylene.
[0015] This invention provides a method for preparing the micro-crosslinking agent, comprising the following steps:
[0016] (1) Using an organic base as a catalyst, an acetate compound reacts with an alkoxyacetaldehyde to prepare a hydroxyl functional group compound; the oil and water phases are separated by acidification with hydrochloric acid aqueous solution.
[0017]
[0018] (2) The oil phase obtained in step (1) is heated and dehydrated under acidic conditions to obtain α,β-unsaturated ester compounds;
[0019]
[0020] (3) Using palladium acetate as a catalyst, triethylamine as a basic reagent and triphenylphosphine as a ligand, α,β-unsaturated ester compounds react with halobenzenes to obtain micro-crosslinking agents.
[0021]
[0022] Preferably, the organic base in step (1) is selected from tert-butyllithium.
[0023] Preferably, the mass ratio of the acetate compound to alkoxyacetaldehyde in step (1) is 1.5-2:1.
[0024] Preferably, the reaction temperature in step (1) is -78℃ to -60℃.
[0025] Preferably, the reaction temperature in step (2) is 120-130℃.
[0026] Preferably, in step (2), p-toluenesulfonic acid provides the aforementioned acidic conditions.
[0027] Preferably, the mass ratio of the halobenzene in step (3) to the alkoxyacetaldehyde in step (1) is 2-3:1.
[0028] Preferably, the reaction temperature in step (3) is 160℃-165℃.
[0029] Preferably, the halogenated benzene in step (3) is selected from chlorobenzene, bromobenzene, and iodobenzene.
[0030] As a preferred embodiment, the ultra-high molecular weight grafted polymer is used in battery separators.
[0031] A battery separator, the raw materials for which are prepared include a micro-crosslinking agent, UHMWPE and peroxide.
[0032] Preferably, the amount of the micro-crosslinking agent is 0.5~1.0%wt relative to the mass of UHMWPE, and more preferably 0.8~1.0%wt.
[0033] Preferably, the amount of the peroxide used is 0.02~0.03%wt relative to the mass of UHMWPE.
[0034] A method for preparing a battery separator includes the following steps: mixing UHMWPE, peroxide, micro-crosslinking agent, and white oil, extruding and casting the mixture in a twin-screw extruder, and winding the film through a casting roller to obtain a 1.0 mm thick film; then placing the film on a static biaxial stretching machine for stretching, with a transverse and longitudinal stretching ratio of 10 times; and then performing ultrasonic extraction in dichloromethane to remove the white oil, thereby obtaining the battery separator.
[0035] Preferably, in the method for preparing the battery separator, the mixing involves preparing a white oil suspension containing 20 wt% UHMWPE, based on UHMWPE.
[0036] Preferably, the peroxide is tert-butyl peroxide.
[0037] Preferably, the screw temperature of the twin-screw extruder is 200~210℃ and the screw speed is 80rpm.
[0038] This invention provides a solution for enhancing the interfacial wettability of ultra-high molecular weight polyethylene by initiating graft copolymerization with a peroxide initiator to form a lithium battery separator with good wettability. Detailed Implementation
[0039] To facilitate understanding of the present invention, the following description, in conjunction with embodiments, will further illustrate the invention. It should be understood that the following embodiments are merely for a better understanding of the invention and do not imply that the invention is limited to these embodiments.
[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0041] Information on some of the raw materials used is shown in Table 1 below:
[0042] Table 1
[0043] Raw material name purity factory Ethyl acetate AR Aladdin propyl acetate AR Aladdin Ethoxyacetaldehyde AR Aladdin Butoxyacetaldehyde AR Aladdin bromobenzene AR Aladdin HCl aqueous solution 10% V / V aqueous solution Comio LDA solution 2mol / L Aladdin
[0044] Example 1:
[0045] (1) First, cool the cryogenic bath to -78°C. Add 60g of ethyl acetate to a clean and dry round-bottom flask. Place the flask in the cryogenic bath and slowly inject 200mL of a hexane solution of tert-butyllithium into it using a syringe. After stirring for 5min, slowly add 35g of methoxyacetaldehyde dropwise and stir for 30min. Then turn off the refrigeration and allow it to naturally warm to room temperature. Quench the solution with 5mL of 10% hydrochloric acid aqueous solution to obtain the upper oil phase. A small sample was separated, and the structure was determined by NMR. Detailed NMR data are as follows: ¹H NMR spectrum (400MHz, DMF-D6) peak positions are: 4.13~4.18 (m, 3H); 3.40~3.65 (m, 3H); 3.30 (s, 3H); 2.3~2.5 (m, 2H); 1.29 (t, 3H); ¹³C NMR spectrum (400MHz, DMF-D6) peak positions are: 173.1; 79.8; 66.4; 61.3; 59.6; 38.3; 14.1.
[0046]
[0047] (2) The upper oil phase sample was then placed in another clean flask, and 5g of p-toluenesulfonic acid and 50mL of toluene were added. The reaction was carried out under negative pressure at 120℃. The reaction progress was calculated based on the volume of water in the distillation flask. The reaction was stopped when the water no longer increased. A small amount of sample was taken for separation, and the structure was determined by nuclear magnetic resonance. The detailed NMR data are as follows: The peak positions of the 1H NMR spectrum (400MHz, DMF-D6) were: 7.07 (s, 1H); 6.04 (s, 1H); 4.20 (q, 2H); 4.04 (d, 2H); 3.30 (s, 3H); 1.36 (t, 3H); The peak positions of the 1C NMR spectrum (400MHz, DMF-D6) were: 166.5; 141.2; 121.8; 76.0; 61.4; 57.8; 14.2; The remaining sample was extracted with sodium hydroxide aqueous solution, and the oil phase was retained.
[0048]
[0049] (3) The above sample was then placed in another clean flask, and 200 mg of palladium acetate catalyst was added. Nitrogen gas was purged, followed by the addition of 5 g of triethylamine and 5 g of triphenylphosphine, and finally 90 g of chlorobenzene. Under nitrogen protection, the mixture was placed in an oil bath and heated under reflux at 163 °C for 24 h. The product was washed with water and separated by column chromatography to obtain the final product. The target product was obtained by nuclear magnetic resonance analysis. The 1H NMR spectrum (400 MHz) was obtained. The peak positions of the DMF-D6 spectrum were: 7.17~7.45 (m, 5H); 6.83 (t, 1H); 4.20 (q, 2H); 4.04 (d, 2H); 3.30 (s, 3H); 1.29 (t, 3H). The peak positions of the carbon NMR spectrum (400MHz, DMF-D6) were: 168.2; 133.5; 128.9; 128.6; 127.9; 69.4; 61.7; 57.8; 14.2.
[0050]
[0051] Example 2:
[0052] (1) First, cool the cryogenic bath to -65℃. Add 80g of butyl acetate to a clean and dry round-bottom flask. Place the flask in the cryogenic bath and slowly inject 200mL of a hexane solution of tert-butyllithium into it using a syringe. After stirring for 5min, slowly add 40g of ethoxyacetaldehyde dropwise and stir for 30min. Then turn off the refrigeration and allow it to naturally warm to room temperature. Quench the solution with 5mL of 10% hydrochloric acid aqueous solution to obtain the upper oil phase. A small sample was separated, and the structure was determined by NMR. Detailed NMR data are as follows: Proton NMR spectrum (400MHz, DMF-D6) peak positions: 4.13–4.18 (m, 3H); 3.88 (q, 2H); 3.40–3.58 (m, 3H); 2.29–2.54 (m, 2H); 1.62 (m, 2H); 1.45 (m, 2H); 1.10 (s, 3H); 0.90 (s, 3H); Carbon NMR spectrum (400MHz, DMF-D6) peak positions: 173.1; 77.3; 66.9; 66.7; 64.9; 38.3; 31.1; 18.9; 15.2; 13.8.
[0053]
[0054] (2) The upper oil phase sample was then placed in another clean flask, and 5g of p-toluenesulfonic acid and 50mL of toluene were added. The reaction was carried out under negative pressure at 120℃. The reaction progress was calculated based on the volume of water in the distillation flask. The reaction ended when the water no longer increased. A small amount of sample was taken for separation, and the structure was determined by nuclear magnetic resonance. The detailed NMR data are as follows: The remaining sample was extracted with sodium hydroxide aqueous solution, and the oil phase was retained. The peak positions of the proton NMR spectrum (400MHz, DMF-D6) are: 7.07 (m, 1H); 6.04 (d, 1H); 3.97~4.04 (m, 4H); 3.50 (q, 2H); 1.62 (m, 2H); 1.45 (m, 2H); 1.10 (t, 3); 0.90 (t, 3H); the peak positions of the carbon NMR spectrum (400MHz, DMF-D6) are: 166.5; 139.3; 121.2; 73.5; 66.2; 65.0; 31.2; 18.9; 15.3; 13.8.
[0055]
[0056] (3) The above sample was then placed in another clean flask, 200 mg of palladium acetate catalyst was added, nitrogen gas was purged, 5 g of triethylamine and 5 g of triphenylphosphine were added, and finally 100 g of bromobenzene was added. Under nitrogen protection, the sample was placed in an oil bath and heated under reflux at a temperature of 165 °C for 24 h. The product was washed with water and separated by column chromatography to obtain the final product. The target product was obtained by nuclear magnetic resonance analysis. The peak positions of the proton NMR spectrum (400MHz, DMF-D6) are: 7.33 (m, 1H); 7.14 (m, 2H); 6.93 (m, 2H); 5.95 (s, 1H); 3.97~4.04 (m, 4H); 3.50 (q, 2H); 1.62 (m, 2H); 1.45 (m, 2H); 1.10 (t, 3H); 0.90 (t, 3H); the peak positions of the carbon NMR spectrum (400MHz, DMF-D6) are: 166.5; 155.1; 135.4; 128.6; 127.9; 126.4; 116.1; 72.5; 66.5; 65.0; 31.2; 18.9; 15.3; 13.8.
[0057]
[0058] Example 3:
[0059] (1) First, cool the cryogenic bath to -75°C. Add 108g of hexyl acetate to a clean and dry round-bottom flask. Place the flask in the cryogenic bath and slowly inject 200mL of tetrahydrofuran solution of tert-butyllithium into it using a syringe. After stirring for 5min, slowly add 55g of butoxyacetaldehyde dropwise and stir for 30min. Then turn off the refrigeration and allow it to naturally warm to room temperature. Quench the solution with 5mL of hydrochloric acid solution to obtain the upper oil phase. A small sample was separated, and the structure was determined by nuclear magnetic resonance (NMR). The peak positions of the proton NMR spectrum (400MHz, DMF-D6) were: 4.13~4.18 (m, 3H); 3.37~3.65 (m, 5H); 2.29~2.54 (m, 2H); 1.31~1.62 (m, 12H); 0.88~0.90 (m, 6H). The peak positions of the carbon NMR spectrum (400MHz, DMF-D6) were: 173.1; 77.6; 70.7; 66.7; 65.2; 38.3; 32.2; 31.5; 28.9; 25.5; 22.7; 19.0; 14.1.
[0060]
[0061] (2) The upper oil phase sample was then placed in another clean flask, and 5g of p-toluenesulfonic acid and 50mL of toluene were added. The reaction was carried out under negative pressure at 120℃. The reaction progress was calculated based on the volume of water in the distillation flask. The reaction ended when the water no longer increased. A small amount of sample was taken for separation, and the structure was determined by nuclear magnetic resonance. The remaining sample was extracted with sodium hydroxide aqueous solution, and the oil phase was retained. The peak positions of the proton NMR spectrum (400MHz, DMF-D6) are: 7.07 (m, 1H); 6.04 (d, 1H); 3.97~4.04 (m, 4H); 3.37 (m, 2H); 1.29~1.51 (m, 12H); 0.88~0.90 (m, 6H); the peak positions of the carbon NMR spectrum (400MHz, DMF-D6) are: 166.5; 139.3; 121.2; 73.8; 65.3; 64.8; 32.3; 31.5; 29.0; 25.5; 22.7; 19.0; 14.1.
[0062]
[0063] (3) The above sample was then placed in another clean flask, 200 mg of palladium acetate catalyst was added, nitrogen gas was purged, 5 g of triethylamine and 5 g of triphenylphosphine were added, and finally 130 g of iodobenzene was added. Under nitrogen protection, the sample was placed in an oil bath and heated under reflux at a temperature of 162 °C for 24 h. The product was washed with water and separated by column chromatography to obtain the final product. The target product was obtained by nuclear magnetic resonance analysis. The peak positions of the proton NMR spectrum (400MHz, DMF-D6) are: 7.33 (m, 1H); 7.14 (m, 2H); 6.93 (m, 2H); 5.95 (S, 1H); 3.97~4.04 (m, 4H); 3.37 (m, 2H); 1.29~1.51 (m, 12H); 0.88~0.90 (m, 6H). The peak positions of the carbon NMR spectrum (400MHz, DMF-D6) are: 166.5; 155.1; 135.4; 128.6; 127.9; 126.4; 116.1; 72.8; 65.1; 65.3; 32.3; 31.5; 29.0; 25.5; 22.7; 19.0; 14.1.
[0064]
[0065] Example 4:
[0066] (1) First, cool the cryogenic bath to -60℃. Add 45g of propyl acetate to a clean and dry round-bottom flask. Place the flask in the cryogenic bath and slowly inject 200mL of tetrahydrofuran solution of tert-butyllithium into it using a syringe. After stirring for 5min, slowly add 50g of hexoxyacetaldehyde dropwise and stir for 30min. Then turn off the refrigeration and allow it to naturally warm to room temperature. Quench with 5mL of hydrochloric acid solution to obtain the upper oil phase. A small sample was separated, and the structure was determined by nuclear magnetic resonance (NMR). The peak positions of the proton NMR spectrum (400MHz, DMF-D6) were: 4.13~4.18 (m, 3H); 3.40~3.65 (m, 2H); 3.37 (m, 2H); 2.29~2.54 (m, 2H); 1.73 (m, 2H); 1.29~1.51 (m, 8H); 0.88 (t, 3H). The peak positions of the carbon NMR spectrum (400MHz, DMF-D6) were: 173.1; 77.6; 71.0; 66.7; 66.2; 38.3; 31.8; 30.0; 22.7; 22.6; 14.1; 10.3.
[0067]
[0068] (2) The upper oil phase sample was then placed in another clean flask, and 5g of p-toluenesulfonic acid and 50mL of toluene were added. The reaction was carried out under negative pressure at 120℃. The reaction progress was calculated based on the volume of water in the distillation flask. The reaction ended when the water no longer increased. A small amount of sample was taken for separation, and the structure was determined by nuclear magnetic resonance. The remaining sample was extracted with sodium hydroxide aqueous solution, and the oil phase was retained. The peak positions of the proton NMR spectrum (400MHz, DMF-D6) are: 7.07 (m, 1H); 6.04 (m, 1H); 4.20 (t, 2H); 4.04 (d, 2H); 3.37 (t, 2H); 1.73 (m, 2H); 1.29~1.51 (m, 8H); 0.88 (t, 3H). The peak positions of the carbon NMR spectrum (400MHz, DMF-D6) are: 166.5; 139.3; 121.2; 73.8; 67.5; 65.1; 31.8; 30.1; 22.7; 22.6; 22.0; 14.1; 10.3.
[0069]
[0070] (3) The above sample was then placed in another clean flask, 200 mg of palladium acetate catalyst was added, nitrogen gas was purged, 5 g of triethylamine and 5 g of triphenylphosphine were added, and finally 105 g of bromobenzene was added. Under nitrogen protection, the sample was placed in an oil bath and heated under reflux at a temperature of 160 °C for 24 h. The product was washed with water and separated by column chromatography to obtain the final product. The target product was obtained by nuclear magnetic resonance analysis. The peak positions of the proton NMR spectrum (400MHz, DMF-D6) are: 7.17~7.40 (m, 5H); 6.83 (t, 1H); 4.20 (t, 2H); 4.04 (d, 2H); 3.37 (t, 2H); 1.29~1.51 (m, 8H); 0.88 (t, 3H). The peak positions of the carbon NMR spectrum (400MHz, DMF-D6) are: 168.2; 133.5; 133.2; 131.6; 128.9; 128.6; 127.9; 74.7; 67.8; 67.2; 23.1; 22.0; 16.3; 15.9; 10.4; 10.3.
[0071]
[0072] Example 5:
[0073] (1) First, cool the cryogenic bath to -70℃. Add 56g of methyl acetate to a clean and dry round-bottom flask. Place the flask in the cryogenic bath and slowly inject 200mL of tetrahydrofuran solution of tert-butyllithium into it using a syringe. After stirring for 5min, slowly add 50g of propoxyacetaldehyde dropwise and stir for 30min. Then turn off the refrigeration and allow it to naturally warm to room temperature. Quench the solution with 5mL of hydrochloric acid solution to obtain the upper oil phase. A small sample was separated, and the structure was determined by nuclear magnetic resonance (NMR). The peak positions of the proton NMR spectrum (400MHz, DMF-D6) were: 4.18 (m, 1H); 3.40~3.70 (m, 8H); 2.29~2.54 (m, 2H); 1.49 (m, 2H); 0.90 (t, 3H). The peak positions of the carbon NMR spectrum (400MHz, DMF-D6) were: 171.5; 77.6; 71.3; 66.7; 51.9; 38.0; 27.3; 10.4.
[0074]
[0075] (2) The upper oil phase sample was then placed in another clean flask, and 5g of p-toluenesulfonic acid and 50mL of toluene were added. The reaction was carried out under negative pressure at 120℃. The reaction progress was calculated based on the volume of water in the distillation flask. The reaction ended when the water no longer increased. A small amount of sample was taken for separation, and the structure was determined by nuclear magnetic resonance. The remaining sample was extracted with sodium hydroxide aqueous solution, and the oil phase was retained. The peak positions of the proton NMR spectrum (400MHz, DMF-D6) are: 7.07 (m, 1H); 6.04 (d, 1H); 4.04 (d, 2H); 3.77 (m, 3H); 3.37 (t, 2H); 1.49 (m, 2H); 0.90 (t, 3H); and the peak positions of the carbon NMR spectrum (400MHz, DMF-D6) are: 166.5; 137.8; 123.0; 74.7; 73.8; 52.0; 23.1; 10.4.
[0076]
[0077] (3) The above sample was then placed in another clean flask, 200 mg of palladium acetate catalyst was added, nitrogen gas was purged, 5 g of triethylamine and 5 g of triphenylphosphine were added, and finally 100 g of bromobenzene was added. Under nitrogen protection, the sample was placed in an oil bath and heated under reflux at a temperature of 162 °C for 24 h. The product was washed with water and separated by column chromatography to obtain the final product. The target product was obtained by nuclear magnetic resonance analysis. The peak positions of the proton NMR spectrum (400MHz, DMF-D6) are: 7.17~7.40 (m, 5H); 6.83 (m, 1H); 4.04 (d, 2H); 3.77 (m, 3H); 3.37 (t, 2H); 1.49 (m, 2H); 0.90 (t, 3H); and the peak positions of the carbon NMR spectrum (400MHz, DMF-D6) are: 168.2; 134.1; 133.5; 130.1; 128.9; 128.6; 127.9; 74.7; 67.2; 52.3; 23.1; 10.4.
[0078]
[0079] Example 6:
[0080] (1) First, cool the cryogenic bath to -75°C. Add 108g of hexyl acetate to a clean and dry round-bottom flask. Place the flask in the cryogenic bath and slowly inject 200mL of tetrahydrofuran solution of tert-butyllithium into it using a syringe. After stirring for 5min, slowly add 55g of hexoxyacetaldehyde dropwise and stir for 30min. Then turn off the refrigeration and allow it to naturally warm to room temperature. Quench the solution with 5mL of hydrochloric acid solution to obtain the upper oil phase. A small sample was separated, and the structure was determined by nuclear magnetic resonance (NMR). The peak positions of the proton NMR spectrum (400MHz, DMF-D6) were: 4.18 (m, 1H); 3.37~3.70 (m, 8H); 2.29~2.54 (m, 2H); 1.29~1.51 (m, 8H); 0.88 (t, 3H). The peak positions of the carbon NMR spectrum (400MHz, DMF-D6) were: 171.5; 77.6; 71.0; 66.7; 51.9; 38.0; 31.8; 30.0; 22.7; 22.6; 14.1.
[0081]
[0082] (2) The upper oil phase sample was then placed in another clean flask, and 5g of p-toluenesulfonic acid and 50mL of toluene were added. The reaction was carried out under negative pressure at 120℃. The reaction progress was calculated based on the volume of water in the distillation flask. The reaction ended when the water no longer increased. A small amount of sample was taken for separation, and the structure was determined by nuclear magnetic resonance. The remaining sample was extracted with sodium hydroxide aqueous solution, and the oil phase was retained. The peak positions of the proton NMR spectrum (400MHz, DMF-D6) are: 7.07 (m, 1H); 6.04 (d, 2H); 4.04 (d, 2H); 3.77 (m, 3H); 3.37 (t, 2H); 1.29~1.51 (m, 8H); 0.88 (t, 3H); the peak positions of the carbon NMR spectrum (400MHz, DMF-D6) are: 166.5; 137.8; 123.0; 73.8; 65.1; 52.0; 31.8; 30.1; 22.7; 14.1.
[0083]
[0084] (3) The above sample was then placed in another clean flask, 200 mg of palladium acetate catalyst was added, nitrogen gas was purged, 5 g of triethylamine and 5 g of triphenylphosphine were added, and finally 110 g of bromobenzene was added. Under nitrogen protection, the sample was placed in an oil bath and heated under reflux at a temperature of 165 °C for 24 h. The product was washed with water and separated by column chromatography to obtain the final product. The target product was obtained by nuclear magnetic resonance analysis. The peak positions of the proton NMR spectrum (400MHz, DMF-D6) are: 7.17~7.40 (m, 5H); 6.83 (t, 1H); 4.04 (d, 2H); 3.77 (s, 3H); 3.37 (t, 2H); 1.29~1.51 (m, 8H); 0.88 (t, 3H). The peak positions of the carbon NMR spectrum (400MHz, DMF-D6) are: 168.2; 134.1; 133.5; 130.1; 128.9; 128.6; 127.9; 67.2; 65.2; 52.3; 31.8; 30.1; 22.7; 14.1.
[0085]
[0086] Contrast with blank spaces:
[0087] Based on Wanhua-U150 material, a white oil suspension containing 20% UHMWPE powder (by mass) was prepared in 30 kg. After thorough stirring, the suspension was extruded and cast in a small twin-screw extruder at a screw temperature of 200℃ and a screw speed of 80 rpm. The film was then wound onto a casting roller to obtain a 1.0 mm thick film. The film was subsequently stretched on a static biaxial stretching machine with a transverse and longitudinal stretch ratio of 10 times. It was then subjected to ultrasonic extraction in dichloromethane to remove the white oil, yielding the battery separator. A 4 μL sample was taken using a micro-injection needle and placed on the separator. After the liquid stabilized, the contact angle was tested according to the method in GB / T30693-2014.
[0088] Example 7:
[0089] Using the product obtained in Example 1 as a crosslinking agent, 10 kg of the product was prepared according to a mass ratio of WH-U150: tert-butyl peroxide: peroxide product from Example 1 of 5000:1:50. 6 kg of the product was taken and added to 24 kg of white oil, stirred thoroughly, and extruded and cast in a small twin-screw extruder at a screw temperature of 200°C and a screw speed of 80 rpm. A 1.0 mm thick film was obtained by winding through a casting roller. The film was then stretched on a static biaxial stretching machine with a transverse and longitudinal stretching ratio of 10 times. It was then subjected to ultrasonic extraction in dichloromethane to remove the white oil, yielding the battery separator. A 4 μL sample was taken using a micro-injection needle and placed on the separator. After the liquid stabilized, the contact angle was tested according to the method in GB / T30693-2014.
[0090] Example 8:
[0091] Using the product obtained in Example 2 as a crosslinking agent, 10 kg of the product was prepared according to a mass ratio of WH-U150: tert-butyl peroxide: product of Example 2 of 5000:1:50. 6 kg of the product was taken and added to 24 kg of white oil, stirred thoroughly, and extruded and cast in a small twin-screw extruder at a screw temperature of 200°C and a screw speed of 80 rpm. A 1.0 mm thick film was obtained by winding through a casting roller. The film was then stretched on a static biaxial stretching machine with a transverse and longitudinal stretching ratio of 10 times. It was then subjected to ultrasonic extraction in dichloromethane to remove the white oil, yielding the battery separator. A 4 μL sample was taken using a micro-injection needle and placed on the separator. After the liquid stabilized, the contact angle was tested according to the method in GB / T30693-2014.
[0092] Example 9:
[0093] Using the product obtained in Example 3 as a crosslinking agent, 10 kg of the product was prepared according to a ratio of WH-U150: tert-butyl peroxide: product of Example 3: 5000: 1:50. 6 kg of the above product was taken and added to 24 kg of white oil, stirred thoroughly, and extruded and cast in a small twin-screw extruder at a screw temperature of 200°C and a screw speed of 80 rpm. A 1.0 mm thick film was obtained by winding through a casting roller. The film was then placed on a static biaxial stretching machine for stretching, with a transverse and longitudinal stretching ratio of 10 times. It was then subjected to ultrasonic extraction in dichloromethane to remove the white oil, yielding the battery separator. A 4 μL sample was taken using a micro-injection needle and placed on the separator. After the liquid stabilized, the contact angle was tested according to the method in GB / T30693-2014.
[0094] Example 10:
[0095] Using the product obtained in Example 4 as a crosslinking agent, 10 kg of the product was prepared according to a mass ratio of WH-U150: tert-butyl peroxide: peroxide product from Example 4 of 5000:1:50. 6 kg of the product was taken and added to 24 kg of white oil, stirred thoroughly, and extruded and cast in a small twin-screw extruder at a screw temperature of 200°C and a screw speed of 80 rpm. A 1.0 mm thick film was obtained by winding through a casting roller. The film was then placed on a static biaxial stretching machine for stretching, with a transverse and longitudinal stretching ratio of 10 times. It was then subjected to ultrasonic extraction in dichloromethane to remove the white oil, yielding the battery separator. A 4 μL sample was taken using a micro-injection needle and placed on the separator. After the liquid stabilized, the contact angle was tested according to the method in GB / T30693-2014.
[0096] Example 11:
[0097] Using the product obtained in Example 5 as a crosslinking agent, 10 kg of the product was prepared according to a mass ratio of WH-U150: tert-butyl peroxide: peroxide product from Example 5 of 5000:1:50. 6 kg of the product was taken and added to 24 kg of white oil, stirred thoroughly, and extruded and cast in a small twin-screw extruder at a screw temperature of 200°C and a screw speed of 80 rpm. A 1.0 mm thick film was obtained by winding through a casting roller. The film was then stretched on a static biaxial stretching machine with a transverse and longitudinal stretching ratio of 10 times. It was then subjected to ultrasonic extraction in dichloromethane to remove the white oil, yielding the battery separator. A 4 μL sample was taken using a micro-injection needle and placed on the separator. After the liquid stabilized, the contact angle was tested according to the method in GB / T30693-2014.
[0098] Example 12:
[0099] Using the product obtained in Example 6 as a crosslinking agent, 10 kg of the product was prepared according to a mass ratio of WH-U150: tert-butyl peroxide: peroxide product from Example 6 of 5000:1:50. 6 kg of the product was taken and added to 24 kg of white oil, stirred thoroughly, and extruded and cast in a small twin-screw extruder at a screw temperature of 200°C and a screw speed of 80 rpm. A 1.0 mm thick film was obtained by winding through a casting roller. The film was then stretched on a static biaxial stretching machine with a transverse and longitudinal stretching ratio of 10 times. It was then subjected to ultrasonic extraction in dichloromethane to remove the white oil, yielding the battery separator. A 4 μL sample was taken using a micro-injection needle and placed on the separator. After the liquid stabilized, the contact angle was tested according to the method in GB / T30693-2014.
[0100] The results are shown in Table 2.
[0101] Table 2
[0102] Comparative Example Contact angle (°) Contrast blank 85 Example 7 30 Example 8 33 Example 9 35 Example 10 32 Example 11 30 Example 12 40
[0103] By comparing different products, it was found that this micro-crosslinking agent can effectively reduce the contact angle and improve the wettability of the electrolyte on the membrane compared to the blank material. However, the chain length in the micro-crosslinking agent does not affect the contact angle between the electrolyte and the membrane.
[0104] It is readily understood that the above embodiments are merely illustrative examples for clear explanation and do not imply that the invention is limited thereto. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A micro-crosslinking agent, as shown in Formula I, I in, R 1 R 2 The functional groups are independent of each other and are saturated hydrocarbon functional groups with C6 or less, preferably methyl, ethyl, or propyl.
2. A method for preparing the micro-crosslinking agent according to claim 1, comprising the following steps: (1) Using an organic base as a catalyst, an acetate compound reacts with an alkoxyacetaldehyde to prepare a hydroxyl-functionalized compound; Acidification with hydrochloric acid solution is used to separate the oil and water phases; (2) The oil phase obtained in step (1) is heated and dehydrated under acidic conditions to obtain α,β-unsaturated ester compounds; (3) Using palladium acetate as a catalyst, triethylamine as a basic reagent and triphenylphosphine as a ligand, α,β-unsaturated ester compounds react with halobenzenes to obtain the target product.
3. The method according to claim 2, characterized in that, The organic base mentioned in step (1) is selected from tert-butyllithium.
4. The method according to claim 2 or 3, characterized in that, The mass ratio of the acetate compound to alkoxyacetaldehyde is 1.5-2:
1.
5. The method according to any one of claims 2-4, characterized in that, The reaction temperature of step (1) is -78℃ to -60℃; and / or the reaction temperature of step (2) is 120-130℃; and / or the reaction temperature of step (3) is 160℃-165℃.
6. The method according to any one of claims 2-5, characterized in that, In step (2), p-toluenesulfonic acid is provided with the aforementioned acidic conditions.
7. The method according to any one of claims 1-6, characterized in that, The mass ratio of the halobenzene in step (3) to the alkoxyacetaldehyde in step (1) is 2~3:
1.
8. The method according to any one of claims 1-7, characterized in that, The halogenated benzene in step (3) is selected from chlorobenzene, bromobenzene, and iodobenzene.
9. A battery separator, wherein the raw materials for its preparation include a micro-crosslinking agent prepared by the method according to any one of claims 1-8, UHMWPE, and peroxide; preferably, the amount of the micro-crosslinking agent is 0.5-1.0%wt relative to the mass of UHMWPE, more preferably 0.8-1.0%wt; and the amount of peroxide added is 0.02-0.03%wt relative to the mass of UHMWPE.
10. The method for preparing the battery separator according to claim 9, comprising the following steps: UHMWPE, peroxide, micro-crosslinking agent, and white oil are mixed, extruded and cast in a twin-screw extruder, and then wound up by casting rollers to obtain a 1.0 mm thick film. The film was then stretched on a static biaxial stretching machine with a stretching ratio of 10 times in the transverse and longitudinal directions. Ultrasonic extraction was performed in dichloromethane to remove the white oil, thus obtaining the battery separator.
Citation Information
Patent Citations
Modification method of ultra-high molecular weight polyethylene and application of ultra-high molecular weight polyethylene in battery diaphragm
CN120795242A